Vitamin E ameliorates oral mucositis in gamma-irradiated rats (an in vivo study) - Salwa Farid Ahmed; Mostafa A. Bakr; Amr H. Rasmy (BMC, 2023)
Abstract Background Radiation therapy is the primary treatment for neck and head cancer patients; however, it causes the development of oral mucositis accompanied by tissue structure destruction and functional alteration. This study was conducted to evaluate the effect of different doses of vitamin E as a treatment for radiationinduced oral mucositis in rat model. Methods 35 male albino rats were randomly divided into five groups: control, untreated radiation mucositis (single dose of 20 Gy), treated radiation mucositis; radiation (single dose of 20 Gy) then vitamin E at doses of 300, 360 and 500 mg/Kg for seven days started 24 h after irradiation. Body weight and food intake were evaluated for each rat. The mucositis score was assessed every day. Rats were sacrificed once at the end of the experiment, and tongue specimens were stained with hematoxylin and eosin, anti P53 and anti Ki67 antibodies. Results Results indicated more food intake and less weight reduction in vitamin E treated groups and the contrary for gamma-irradiated group. Additionally, vitamin E delayed the onset and decreased the severity and duration of mucositis. It also restored the histological structure of lingual tongue papillae. Vitamin E treated groups showed a significant higher Ki67 and lower P53 expression as compared to untreated radiation group. The overall improvement increased as vitamin E dose increased. Finally, the amelioration can be attributed to the decreased apoptosis and increased proliferation of cells. Conclusions Vitamin E especially at dose of 500 mg/Kg could be an effective treatment for radiation-induced oral mucositis.